Prospective cohort study of broccoli consumption frequency and all-cause and cause-specific mortality risks - Liu, Xiangliang; Chang, Yu; Li, Yuguang; Zhang, Xinwei; Li, Fangqi; Song, Jia; Shi, Hanping; Chen, Xiao; Cui, Jiuwei (Frontiers in Nutrition, 2024)
Background: Broccoli is rich in vitamins, minerals and antioxidants with broad health benefits, but its intake frequency and dose-response relationship with mortality risk remains unclear.Methods: Using data from the U.S. National Health and Nutrition Examination Survey 2003-2006, 12486 adults were included. Broccoli intake frequency was evaluated by food frequency questionnaire, and all-cause and cause-specific mortality risks were followed up. The relationship between broccoli intake and mortality risk was analyzed using Cox models.Results: Compared with never consumption, different frequencies of broccoli consumption were associated with significantly decreased risks of all-cause mortality (P for trend <0.001). Consuming broccoli 1-2 times per week was associated with 32%-43% lower mortality risk. More frequent broccoli consumption was negatively correlated with cardiovascular and cancer mortality risks (P<0.05). Consuming broccoli 1-2 times per week for males and ≥3 times per week for females could significantly reduce all-cause mortality risk.Conclusions: Moderate frequent consumption of broccoli may reduce risks of all-cause and cause-specific mortality. Optimal intake frequencies may differ by gender.